Life cycle assessment of the production of xanthate salts and of their application for ARD mitigation - Kunene, Makhosazane Chucky (Department of Chemical Engineering, 2015)
Xanthate salts are commonly used as collectors in the mineral processing of sulphide ores. In more recent studies, xanthate has also been used in the environmental desulphurisation flotation of sulphidic mine tailings and coal waste, with a view to mitigating acid rock drainage (ARD) risks through the pre-disposal removal of sulphide minerals. In South Africa, xanthate salts are produced by Senmin® International (Pty Ltd) via the conversion of carbon disulphide at its facility in Sasolburg. In 2010, Senmin® commissioned a new state-of-the art plant for the production of carbon disulphide using methane rather than charcoal as a carbon source. Although this process has many advantages over the old process, no attempt has been made to date to quantify the environmental benefits. Similarly, whilst the technical feasibility of using xanthate salts in the desulphurisation flotation to reduce the ARD generating potential of mine tailings has been demonstrated in a number of case studies, little attention has been given to the broader environmental implications of this tailings treatment option. The life cycle assessment (LCA) approach proves to be a valuable tool to study the environmental aspects and potential impacts throughout the life cycle of a product or process. In this study, LCA was used as a tool to assess the implications of the new carbon disulphide production process on the environmental performance of subsequent xanthate salt production, as well as the environmental consequences of using these salts in the downstream desulphurisation of base metal sulphide tailings. The objectives of the study were achieved by conducting two inter-related LCA studies: LCA of xanthate production (LCA 1) and LCA of ARD mitigation (LCA 2). These LCA studies followed the protocol set out in the ISO 14040 standards using the Simapro software package (version 7.3.3). The first LCA study was a cradle-to-gate comparison of current and previous carbon disulphide production processes for the production of xanthate. Data was collected in two ways: the foreground data was sourced at the plant in Sasolburg, whilst ecoinvent database was used for background data for the production of 1 tonne of carbon disulphide. To quantify the identified environmental impacts, namely climate change, terrestrial acidification, human toxicity, freshwater ecotoxicity and fossil depletion, ReCiPe, a midpoint life cycle impact assessment (LCIA) method was chosen. Study results confirmed that the new carbon disulphide production facility has a significantly lower environmental foot print than the old charcoal-based process, based on the studied environmental impacts. This improvement reflected positively on the environmental performance of the subsequent xanthate production process